The evaluation of groundwater use applied to municipal water reosurce management - Benetello, Thalita (2021)
The region containing the Piracicaba, Capivari and Jundiaí Watershed demonstrates a growing demand for exploration and groundwater use, which accompanies the increase in population and urbanization. Regional surveys indicate a scenario of limitated availability in groundwater associated with the large volumes of water currently being extracted, demonstrating the need for monitoring, on a local sale, the situation of the use of these water resources. Therefore, this study aimed to evaluate available data on groundwater, at a municipal scale, in order to make a diagnosis of the sustainability of water use. The municipality o Sumaré-SP was selected as it is located in a critical area in terms of water availability and because it includes guidelines for integrated environmental management in its Master Plan. Based on data from official registers of wells, the most exploited aquifers were evaluated in terms of their water potential (flows and specific capacities – average and mean; well depth and water levels); the type of water use; density of wells and the intensity of groundwater extraction; water balance. The existence of areas with water deficit led to recommendations such as the improvement of hydrogeological studies, as well as the monitoring of the increase in water exploitation in the city and the occurrence of conflicts of use.